All these poses, such beautiful Poses: articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright’s direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an “utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo.”1 Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright’s musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the “Clone.” In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.

Sobre meninos e homens Por uma leitura edipiana: Rufus Wainwright e a canção Dinner at Eight [Des garçons et des hommes: Rufus Wainwright et la chanson "Dinner at Eight"] - Júnio, José Mariano Tavares (Cadernos do LINCC, 2008)
O artigo reflete sobre a obra do compositor novaiorquino Rufus Wainwright iconsiderando as suas influências no sentido de explicar, ao menos em parte, a originalidade melódica e harmônica presente na arquitetura de suas canções, a grandiloqüência dramática dos arranjos, e a complexidade de sua persona artística, opondo, a uma forte teatralidade camp, a melancolia trágica, cortante, do solitário e outsider.

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.